2011
DOI: 10.1371/journal.pone.0019838
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Massively Parallel Sequencing for Detecting Candidate Infectious Agents Associated with Human Tissue

Abstract: Massively parallel sequencing technology now provides the opportunity to sample the transcriptome of a given tissue comprehensively. Transcripts at only a few copies per cell are readily detectable, allowing the discovery of low abundance viral and bacterial transcripts in human tissue samples. Here we describe an approach for mining large sequence data sets for the presence of microbial sequences. Further, we demonstrate the sensitivity of this approach by sequencing human RNA-seq libraries spiked with decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 16 publications
1
56
0
1
Order By: Relevance
“…Illumina RNA-seq libraries were constructed, barcoded, and pooled, and two lanes of paired-end sequencing data were obtained using the Illumina GAIIx platform. Reads were filtered for base quality and low complexity, then aligned pairwise to human rRNA and cDNA (Flicek et al 2011) and genome (hg18) reference sequences using Burrows-Wheeler Aligner (BWA) (Li and Durbin 2010), as previously described (Moore et al 2011). Aligned reads were removed from the data set, leaving 34.9 million pairs (Supplemental Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Illumina RNA-seq libraries were constructed, barcoded, and pooled, and two lanes of paired-end sequencing data were obtained using the Illumina GAIIx platform. Reads were filtered for base quality and low complexity, then aligned pairwise to human rRNA and cDNA (Flicek et al 2011) and genome (hg18) reference sequences using Burrows-Wheeler Aligner (BWA) (Li and Durbin 2010), as previously described (Moore et al 2011). Aligned reads were removed from the data set, leaving 34.9 million pairs (Supplemental Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven colorectal tumor samples and 11 matched normal samples were processed, as detailed previously (Moore et al 2011), using an RNeasy Plus mini kit (QIAGEN) to purify total RNA or an AllPrep DNA/RNA mini kit (QIAGEN) to purify both DNA and RNA. RNA quality and concentration were assessed using Agilent Bioanalyzer 2000 RNA Nanochips.…”
Section: Metagenomic Library Construction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to metagenomic analysis using pyrosequencing, Illumina short-read sequencing enables a greater depth (by an order of magnitude) that is reflected in a very low detection limit. A recent report revealed that viral transcripts could be found at frequencies of Ͻ1 in 1,000,000 (28). However, because of short reads, de novo assembly without any reference is difficult to conduct, so it is not suitable for discovering an unknown viral genome.…”
Section: Discussionmentioning
confidence: 99%
“…Although Fusobacterium species are part of the gut microbiome in human, their invasive [1,2], adherent [3,4], and pro-inflammatory [5][6][7] features have been noted. Fusobacterium have been associated with inflammatory disorders such as periodontitis [8], cerebral abscesses [9], acute appendicitis [10] and inflammatory bowel diseases [1,11,12].…”
Section: Introductionmentioning
confidence: 99%